Серия переломов, подвергнутых лечению в Медико-механическом интституте за 1916 г. (V серия историй болезни) - Вегнер К.Ф.; Vegner K.F. (Мирный труд, 1916)
Описи історій хвороб пацієнтів Медико-механічного інституту

Descriptions of patient histories of the Medical-Mechanical Institute
A series of fractures treated at the Medico-Mechanical Institute in 1916 (V series of case histories)